Effectiveness of red propolis and Mikania glomerata in bitches´s surgical analgesia (Research, Society and Development, 2020)
The aim of this research was to evaluate the analgesia provided by red propolis and Mikania glomerata oral administration in 40 female dogs submitted to ovariohysterectomy (OH) compared to standard treatment with no steroidal anti-inflammatory ketoprofen. Through of a doble-blind and randomized study, the animals were divided in four different groups with 10 animals of treatments: control treatment with ketofen (CT), propolis treatment (PT), Mikania glomerata treatment (MT), and propolis-Mikania glomerata treatment (PGT). All pacients received one of these treatments two hours before OH and the pain evaluation was performed 1 (T1), 6 (T6), 12 (T12), and 24 hours (T24) after OH using University of Melbourne Pain Scale and the Glasgow Composite Measure Pain Scale. Glucose levels were also measured at the same times, except at 6 hours after OH (T6). All treatments achieved similar and satisfactory analgesia. During the experiment, only three animals were rescued, two belonging to the PT and another of the MT. Considering the lower rate of complications and no rescue necessity of in PGT and CT treatments, they were considered the most effective and safer. The combined treatment with propolis and Mikania glomerata could  be a promising alternative method for OH surgery analgesia in bitches.